When Consumers Do Not Recognize “Benign” Intention Questions as Persuasion Attempts - Williams, Patti; Fitzsimons, Gavan J.; Block, Lauren G. (Journal of Consumer Research, 2004)
We demonstrate that the mere-measurement effect occurs because asking an intention question is not perceived as a persuasion attempt. In experiments 1 and 2, we show that when persuasive intent is attributed to an intention question, consumers adjust their behavior as long as they have sufficient cognitive capacity to permit conscious correction. In experiment 3 we demonstrate that this finding holds with product choice and consumption, and we find that persuasion knowledge mediates the effects. In experiment 4, we show that when respondents are educated that an intention question is a persuasive attempt, the behavioral impact of those questions is attenuated.